Kristy's great idea - Martin, Ann M., 1955- (New York : Scholastic, 1986)
Follows the adventures of Kristy and the other members of the Baby-sitters Club as they deal with crank calls, uncontrollable two-year-olds, wild pets, and parents who do not always tell the truth.
"An Apple paperback.".
5.3
3-6
Keywords: Babysitters -- Fiction; Friendship -- Fiction; Stepfamilies -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Stepfamilies -- Fiction